Synthesis and Antibacterial Activity of 2,3-Dihydro-4-(2’-Hydroxy-3’-Bromo-5’-Ethylphen-1’-yl)-2-Substitutedphenyl-1,5-Benzothiazepine Derivatives - Naik, V.R.; Naik, H.B. (Asian Journal of Chemistry, 2010)
2-Aminothiophenol reacts with 2´-hydroxy chalcones in methanol and acetic acid to give propiophenones which immediately undergo cyclization to give 1,5-benzothiazepine derivatives. The structures of the compounds have been confirmed by elemental analysis and spectral analysis. The antibactarial activity of the compounds have been also screened.